2012
DOI: 10.2466/10.06.25.pms.115.5.521-533
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Physical Activity with Driving-Related Cognitive Abilities in Older Drivers: An Exploratory Study

Abstract: Summary.-the purpose of this study was to examine the associations between physical activity and driving-related cognitive abilities of older drivers. thirtyeight female and male drivers ages 61 to 81 years (M = 70.2, SD = 5.0) responded to the International Physical Activity Questionnaire and were assessed on a battery of neuropsychological tests, which included measures of visual attention, executive functioning, mental status, visuospatial ability, and memory. A higher amount of reported physical activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Similarly, professionally supervised exercise training three times per week significantly lessened depression in PLWHIV [ 63 ]. Our findings show that depression scores dropped consistently immediately following exercise and during the 3 months rest from structured physical activity, suggesting that depression may be an independent modulator of QoL amongst individuals with HAND, similar to other studies [ 64 , 65 ]. Therefore, interventions aimed at alleviating depression symptoms amongst persons with HAND may improve their QoL.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, professionally supervised exercise training three times per week significantly lessened depression in PLWHIV [ 63 ]. Our findings show that depression scores dropped consistently immediately following exercise and during the 3 months rest from structured physical activity, suggesting that depression may be an independent modulator of QoL amongst individuals with HAND, similar to other studies [ 64 , 65 ]. Therefore, interventions aimed at alleviating depression symptoms amongst persons with HAND may improve their QoL.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, more vigorous PA led to better performance on the Useful Field of View test (widely used to assess peripheral vision). Other studies conducted with older participants [86,71,89] also reported an association between PA and better scores on the Useful Field of View test. The two latter studies [71,89] did not evaluate the PA itself, but used questionnaires to collect information about the participants' PA.…”
Section: Visuospatial Attentionmentioning
confidence: 80%
“…8,9 Indeed, studies have directly suggested that physical activity may be necessary to preserve driving-related cognitive abilities. 10,11 Perhaps of greatest importance, physical activity improves musculoskeletal fitness and energy levels, 12,13 which may have a more immediate effect on driving responsiveness. In fact, in many studies working to develop and evaluate screening tests, physical activity has been tested as a marker for both physical and cognitive driving readiness.…”
Section: Introductionmentioning
confidence: 99%